2017
DOI: 10.1007/s00380-017-1041-0
|View full text |Cite
|
Sign up to set email alerts
|

Shocks after implantable cardioverter-defibrillator implantation in idiopathic cardiomyopathy patients: a myocardial biopsy study

Abstract: Prediction of follow-up shock is crucial to stratify patients with dilated cardiomyopathy (DCM) requiring implantable cardioverter defibrillator (ICD). The objective of the article is to assess the predictive value of endo-myocardial biopsy (EMB) towards ICD shock and follow-up mortality. A series of patients with DCM scheduled for ICD implantation underwent EMB to further determine the genesis of DCM. Presence of fibrosis and inflammation was documented and related to outcomes. A total of 240 patients were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…In the cardiac MRI study carried out by Wu et al, it was reported that myocardial scar tissue increased the frequency of ICD shock in NICMP 11 . The study conducted by Safak et al stated that the presence of inflammation was decisive in endomyocardial biopsy in idiopathic cardiomyopathy patients in appropriate ICD shocks 23 . Also it has been showed that inflammation, and myocardial stretch, is associated with myocardial damage and fibrosis which predispose arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiac MRI study carried out by Wu et al, it was reported that myocardial scar tissue increased the frequency of ICD shock in NICMP 11 . The study conducted by Safak et al stated that the presence of inflammation was decisive in endomyocardial biopsy in idiopathic cardiomyopathy patients in appropriate ICD shocks 23 . Also it has been showed that inflammation, and myocardial stretch, is associated with myocardial damage and fibrosis which predispose arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…(2018 г.) у пациентов с признаками активного миокардита, по данным ЭМБ, частота оправданных срабатываний оказалась достоверно меньше, чем при его отсутствии (p=0,04), что свидетельствует о том, что при активном миокардите у большинства пациентов торопиться с имплантацией ИКД не стоит [31]. В нашем исследовании при изолированном миокардите срабатывание дефибриллятора зарегистрировано лишь в одном случае, существенно большее число шоков отмечалось при сочетании генетической кардиомиопатии и миокардита (70%).…”
Section: Discussionunclassified
“…В то же время в работе H-P. Schultheiss (2018) и соавт. у пациентов с признаками активного миокардита, по данным ЭМБ, частота оправданных срабатываний оказалась статистически значимо меньше, чем при его отсутствии (p=0,04), что свидетельствует о том, что в острый период в большинстве случаев не стоит торопиться с имплантацией [21].…”
Section: Discussionunclassified